Persepsi Mahasiswa Pendidikan Akuntansi Terhadap Tantangan Utama Dalam Penerapan Etika dan Implementasi di Pengajaran Akuntansi - Syalwa, Nayoebi Layla; Rahayu, Nacha Dwi; Devlani, Nazifa; Aulia, Zahra (Jurnal Cerdik: Jurnal Pendidikan dan Pengajaran, 2024)
This study aims to analyze accounting students' perceptions of the main challenges in understanding and applying ethics in accounting teaching and to explore effective implementation strategies. A qualitative approach was employed, with data collected through questionnaires. The results indicate that students face significant challenges in applying ethical teaching concepts, particularly in demonstrating good behavior, motivating others to actively participate in learning, and providing guidance to enhance others' self-confidence. Most students agree that case discussion methods are an effective approach to improving their understanding of teaching ethics. The discussion highlights the need to integrate ethics into teaching methods that align with students' needs. This study is expected to contribute to developing more ethical and realistic teaching strategies.